Case Report: Early Identification of Subclinical Cardiac Tamponade in a Patient With a Left Ventricular Assist Device by the Use of Sublingual Microcirculatory Imaging: A New Diagnostic Imaging Tool? - Akin, Sakir; Ince, Can; Struijs, Ard; Caliskan, Kadir (Frontiers in Cardiovascular Medicine, 2022)
Clinical diagnosis of cardiac tamponade can be difficult in patients with continuous flow left ventricle assist devices (cf-LVADs). This is even more so because of the lack of adequate bedside echocardiographic windows. Previous studies on monitoring sublingual microcirculation showed deterioration of end-organ perfusion in patient with cardiogenic shock. In this paper we report alterations in the sublingual microcirculation in a cf-LVAD patient prior to clinical manifestation of tamponade. Our case report suggests that such real-time monitoring of the microcirculation may provide a new diagnostic modality for early recognition of cardiac tamponade.